2021
DOI: 10.1097/nmd.0000000000001367
|View full text |Cite
|
Sign up to set email alerts
|

Moral Injury and Burnout in Health Care Professionals During the COVID-19 Pandemic

Abstract: The coronavirus pandemic (COVID-19) is predicted to increase burnout in health professionals (HPs), but little is known about moral injury (MI) in this context. We administered the Moral Injury Symptoms Scale for Health Professionals (MISS-HP) and the abbreviated Maslach Burnout Inventory via online survey to a global sample of 1831 HPs in April and October 2020. Mean MISS-HP increased from 27.4 (SD, 11.6) in April to 36.4 (SD, 13.8) in October (p < 0.001), with an accompanying increase in personal accomplishm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(99 citation statements)
references
References 62 publications
5
92
2
Order By: Relevance
“…22,26,27 Across separate cohorts of HPs in 2020, the level of moral injury increased dramatically, and functional impairment from moral injury symptoms nearly doubled. 14 This qualitative study adds additional context to these numbers; the emotions reported-isolation, alienation, betrayalsignificantly overlapped with the symptoms of moral injury in military and veteran populations. 28 Some respondents who had expressed these emotions were so distressed to the point where their entire lives had changed dramatically, whereas others who have experienced the same events were disturbed but not as affected in their functioning.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…22,26,27 Across separate cohorts of HPs in 2020, the level of moral injury increased dramatically, and functional impairment from moral injury symptoms nearly doubled. 14 This qualitative study adds additional context to these numbers; the emotions reported-isolation, alienation, betrayalsignificantly overlapped with the symptoms of moral injury in military and veteran populations. 28 Some respondents who had expressed these emotions were so distressed to the point where their entire lives had changed dramatically, whereas others who have experienced the same events were disturbed but not as affected in their functioning.…”
Section: Discussionmentioning
confidence: 91%
“… 9 Both mental health disorders and burnout are projected to increase among clinicians in the wake of the pandemic 11 , 12 , 13 ; early evidence suggests that increases in moral injury may be a bellwether of a workforce under tremendous strain. 14 …”
Section: Introductionmentioning
confidence: 99%
“…There are also several personal, behavioral, and situational factors that characterize the presence of MI in healthcare professionals. These include younger age (Mantri et al, 2021b;Wang et al, 2021), female gender (Wang et al, 2021), the unmarried (Wang et al, 2021), the divorced (Mantri et al, 2021b), those with lower religiosity (Mantri et al, 2021a(Mantri et al, , 2021b, Buddhist or Taoist religion (vs. no religion) (Wang et al, 2021), involvement in the care of COVID-19 patients (Mantri et al, 2021b;Wang et al, 2021), nurses (vs. physicians) (Mantri et al, 2021b), higher levels of burnout or emotional exhaustion (Mantri et al, 2021a(Mantri et al, , 2021bWang et al, 2020Wang et al, , 2021, and exposure to workplace violence (Wang et al, 2020(Wang et al, , 2021. As in studies of military personnel, depression and anxiety symptoms have been significantly correlated with MI in each of the studies above (except when controlling for HCP burnout).…”
Section: Healthcare Settingsmentioning
confidence: 99%
“…That is, novel kinds of incidence effects on low mental health, but not on sleep, emerged over time. Earlier Covid-19 studies have highlighted sleep problems [3,4] and moral injuries in healthcare workers [7], but we may already begin to see diffuse downstream mental-health effects of these early indicators of prolonged stress in this one-year follow up. As the pandemic prolongs, transient stress reactions and accumulating adversity may increasingly predict differential health outcomes.…”
Section: Discussionmentioning
confidence: 78%
“…Many healthcare workers may have experienced a double burden of stress from Covid-19 compared to the general population given their (at least) comparable risk to own health and the additional work stress deriving from high prevalence of patients with infectious diseases [7]. It has been shown that workload due to infections-related hospital ward overcrowding may lead to depression and sickness absence in healthcare staff [8][9][10].…”
Section: Introductionmentioning
confidence: 99%